Pemberdayaan Wanita Tani Untuk Mitigasi Pertanian Skala Mikro Pada Budidaya Tanaman Obat Keluarga (Toga) di Masaran Kab. Sragen - triyono, kharis; Sumarmi, Sumarmi; Indriastuti, Dorothea Ririn (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
The Community Partnership Program (PKM) activity partners are people who are not economically productive (general/ordinary people) Farming Women's Group « Subur Makmur » located in Siododadi Village, Masaran District, Sragen Regency. The problems faced are low agricultural production due to a lack of fertilizer due to the scarcity and high price of chemical fertilizers and due to attacks by plant pests and diseases. Therefore, it is necessary to empower women farmers to overcome these problems, namely by carrying out micro-scale mitigation (prevention) in their farming businesses. The objectives of this community partnership program (PKM) are: 1) improving the skills, knowledge and attitudes of partners in managing farming businesses, 2) motivating partners to always be creative and innovative in managing farming businesses, 3) encouraging partners to improve and maintain their farming businesses by utilizing environmentally friendly local resources and 4) for universities as a form of implementing MBKM based on the second and third Main Performance Indicators (IKU), namely students and lecturers active outside campus. The methods that will be used to achieve this goal are outreach to community leaders and partners, providing knowledge and skills through lectures, field practice, discussions, and assistance in making liquid organic fertilizer (POC) and vegetable pesticides as well as planting family medicinal plants (Toga) in pot. The output targets of this community partnership program are: 1) Women farmer groups (KWT) as partners can become pioneers in managing environmentally friendly farming businesses, 2) be able to make their own POC and vegetable pesticides, 3) have skills and knowledge in mitigating the business farming, and 4) publication through national journals with ISSN in the Adi Widya Journal with ISSN 2598-2273 (print media) and ISSN 2598-2281 (online media) which have been indexed by Sinta and online mass media and Yuotube